Pygopagus Twins Separation Using a Rectangular Fasciocutaneous Flap: Case Report From Beirut, Lebanon - Christopher Hakim, MD; Saif Emsieh, MD; Edwin Chrabieh; Jana Zeineddine, MD; Amir Ibrahim, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Conjoined twins, although rare, present unique challenges in surgical management, particularly regarding skin closure after separation. This case report details the successful separation of pygopagus conjoined twins using a rectangular skin flap technique. The twins, joined at the lumbar and sacral regions, underwent meticulous preoperative planning and collaborative effort from multiple medical teams. The surgery involved raising fasciocutaneous rectangular flaps over the buttocks, spine separation, rectal division, and reconstruction of pelvic floor muscles. The primary skin closure was achieved successfully. This case highlights the superior gluteal-based rectangular flap technique in such a separation and the importance of multidisciplinary approaches in improving outcomes for complex surgeries.